Strengthening of Occupational Health Surveillance and Prevention System Using Social Enterprise Concept - Kuttiyawithayakoon, Siriwan; Pruankratoke, Unchulee; Mungaomrlang, Anek (Journal of Health Science of Thailand, 2017)
Cases of occupational related diseases reported into national surveillance system are lower than the actual occurrences. This is caused by the complexity of the system and the lack of trust of private sector to government sector. The research team tried utilizing social enterprise (SE) concept in solving these problems. This research was done for 12 months by using marketing operation research methodology and consisted of founding an SE company to provide dispensing room services in the operations and developed an occupational health surveillance and prevention system by changing the dispensary room into the starting point of the system. In the beginning, there were 3 companies, with 12,500 workers, participated. The system was able to detect and control of spreading of 3 incidences; 3 cases and 5 cases of influenza in company A and company B, respectively, and 2 cases of conjunctivitis in company C. The research team participated in the investigation of a fatal traffic accident and drove to the installation of GPS devices in the vehicles to monitor and analyze the company driver’s behavior. The SE business in the 3 operations was profitable and 3 more operations participated, increasing the total number of workers to 24,300. This research proves that the SE concept is an alternative for increasing potential of the existing surveillance system. However, if it is to be used in other areas it must be carefully and thoroughly scrutinized in all dimensions.